History as performance: pupil perspectives on history in the age of 'pressure to perform'. Issue 3 (3rd April 2019) - Samuelsson, Johan
ABSTRACT: The development a standard-based curriculum in History can be related to the school reforms where 'performance' are crucial principles. The aim is to analyse pupils' perspectives on the relation between their views on historical knowledge and the national test in History and grading. When the pupils in this study – directly after taking a national test in History – were asked to reason about what historical knowledge is, another subject emerged: a collective memory subject. History as 'performance' emerges clearly in connection with the pupils' discourse on grades and History, which has an emphasis on 'working', 'writing', and 'doing homework' to get a better grade in History. The disciplinary knowledge content specified in the curricula does not correspond to pupils' experiences of what the central historical knowledge is in national tests and grading. It is apparent that disciplinary knowledge content is 'under pressure' in the age of performance.